Relationships between personal qualities, organizational functions, environmental factors, and success of entrepreneurs in Iranian small manufacturing firms. - Maharati, Yaghoob (2011)
Scholars and practitioners constantly report on the significance of research on entrepreneurship in upholding the performance of small industries. Nevertheless, little has been established in the literature on entrepreneurial studies in the Iranian context. Hence, this has induced the present research to explore the relationship between personal qualities, organizational functions, and environmental apprehension with a moderator role of national culture on the success of entrepreneurs in small manufacturing firms in Iran. To fulfill the aims of the research,a quantitative research design with self-administered questionnaire was employed. The respondents were selected from the directory of small manufacturing firms provided by Iran Small Industries & Industrial Parks Organization (ISIPO). Based on the probability sampling design, 600 entrepreneurs were chosen across all the regions in Iran to participate in the study. The mail survey yielded 240 completed responses, which were included in the final analysis. The objectives of the study were reviewed using appropriate descriptive and inferential statistical procedures. The results of the analysis revealed that entrepreneurs with high need for achievement, high level of risk taking, and high locus of control are more successful than those with low level of these qualities. On the other hand, this study found a significant positive linear relationship between personal qualities and entrepreneurs’ success in terms of growth (i.e., sales, employee, and profit) and survival. Interestingly, the relationship between organizational function, governmental support system, and entrepreneurs’ success was found to be significant, positive, and linear. Besides, the relationship between personal qualities and entrepreneurs’ success in terms of growth was completely found to be moderated by the national culture (i.e., human orientation, assertiveness,and performance orientation) within the small manufacturing firms in Iran. In addition, the findings of this study spawn remarkable implications for both the theory and practices. This study supports previous research findings that small entrepreneurial companies’ success is a multi-dimensional construct. Thus, the success of entrepreneurs in small companies needs to be addressed at individual, organizational, and environmental levels. Furthermore, the moderating role of national culture remains vital and cannot be compromised in future research. Hofstede’s extended framework, i.e., the Global Leadership and Organizational Behaviour Effectiveness (GLOBE) research programmed, which was adopted in this study, proves that the acquaintance on national culture helps entrepreneurship progression.